Recommendation: Treatment of clinical long COVID encephalopathies with nasal administered mesenchymal stromal cell extracellular vesicles - Askenase, Philip W. (Frontiers in Nanotechnology, 2022)
We propose therapy with extracellular vesicles (EVs) for dominant central nervous system aspects of chronic Long COVID Syndromes (LCS). These clinical conditions have a delayed onset of 1–3 months following the cessation of active SARS-CoV-2 virus infections that cause an acute disease called COVID-19. The therapy of LCS will be achieved by direct access to the central nervous system (CNS) by nasal administration of small EVs derived from Mesenchymal Stromal Cells (MSC). When administered nasally, they target CNS microglia and endothelia involved in LCS encephalopathy, as indicated by experimental animal models and human autopsy and spinal fluid studies. Underlying this approach is the discovery that MSC-sEV treatment for healing neuro injury targets, microglia, and macrophages that then likely release secondary trophic EVs that affect the local capillary endothelial cells to restore vascular integrity. It is postulated that the pathways of endothelial and neural pathologies in acute SARS-CoV-2 virus infections may carry over to produce underlying vascular and neurological defects mediating LCS that are susceptible to this proposed nasal therapy with MSC-sEVs.